2004
DOI: 10.1111/j.1473-4192.2004.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of advanced foreign language proficiency: Internet‐mediated German language play

Abstract: Adult foreign language play has been an under‐explored phenomenon in the field of applied linguistics, despite the fact that strong claims have been made about its importance in instructed foreign language learning. This article documents the nature of adult foreign language play in the electronic medium and examines the ways in which computer‐mediated communication may afford opportunities for its occurrence. It is further argued that examination of this phenomenon provides insights into issues of advanced fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 70 publications
0
56
0
Order By: Relevance
“…On the other hand, learners inevitably engage in a variety of additional communicative actions beyond classroom tasks such as personal relationship building, intercultural misunderstandings, delegation of project tasks, directions for the use of project mediating software, disagreements, and discussion of popular culture topics. TC communicative actions that have been researched (see Belz, 2007 for a review) range from language play (Belz & Reinhardt, 2004) and flirting (Belz & Kinginger, 2002) to crying (O'Dowd, 2006) to conflict (Belz, 2003b;Schneider & von der Emde, 2006). Participating in these communicative actions requires a broad array of interpersonal linguistic features (Biber, 1988).…”
Section: Pragmatic and Interpersonal Linguistic Featuresmentioning
confidence: 99%
“…On the other hand, learners inevitably engage in a variety of additional communicative actions beyond classroom tasks such as personal relationship building, intercultural misunderstandings, delegation of project tasks, directions for the use of project mediating software, disagreements, and discussion of popular culture topics. TC communicative actions that have been researched (see Belz, 2007 for a review) range from language play (Belz & Reinhardt, 2004) and flirting (Belz & Kinginger, 2002) to crying (O'Dowd, 2006) to conflict (Belz, 2003b;Schneider & von der Emde, 2006). Participating in these communicative actions requires a broad array of interpersonal linguistic features (Biber, 1988).…”
Section: Pragmatic and Interpersonal Linguistic Featuresmentioning
confidence: 99%
“…The learning of foreign language forms which language learners first encounter outside in the inter-psychological plane, shows one example of internalization (Belz & Reinhardt, 2004) "i.e. knowledge moving from "out there" to "in there" (p. 328).…”
Section: Internalization and Private Speechmentioning
confidence: 99%
“…Cook 1997G. Cook , 2000Lantolf 1997;Sullivan 2000;Tarone 2000;Broner and Tarone 2001;Belz 2002aBelz , 2002bBelz and Reinhardt 2004;Bell 2005). Following Kramsch (2000), Belz criticizes the tendency of teachers and researchers to focus predominantly on the grammatical correctness or denotational content of learner utterances, while ignoring the other functions of language as a semiotic system (i.e.…”
Section: Ideologies Of Language Use In Fl Classroomsmentioning
confidence: 99%
“…Briefly, he argued that a 'monocompetent' individual has perfect (100 per cent) knowledge of a particular language, while a 'multicompetent' person is 100 per cent in L1 plus whatever expertise he/she has gained in an additional language. Building on this construct, Belz (2002aBelz ( , 2002bBelz and Reinhardt 2004) examined the language play that occurred when students in a third year German course were asked to write texts in German and at least one additional language. This work demonstrated that rather than switching languages to make up for some deficiency, learners, at times, switched playfully and purposively at all levels of language.…”
Section: Language Play and Language Knowledgementioning
confidence: 99%
See 1 more Smart Citation